2022
DOI: 10.7759/cureus.22280
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Performance on the United States Medical Licensing Examination Step 2 Clinical Knowledge: A Systematic Literature Review

Abstract: In February 2020, the governing bodies of the United States Medical Licensing Examination (USMLE) announced the decision to change Step 1 score reporting from a three-digit system to pass/fail designation. Previous studies theorized that Step 2 Clinical Knowledge (CK) will become the numerical standard by which residency directors can quickly sort through program applicants. The goal of this study is to review prior research and identify significant factors associated with Step 2 CK outcomes.A systematic liter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 40 publications
1
9
0
Order By: Relevance
“…[ 19 , 20 ] Furthermore, one systematic review also showed negative correlation between age and United States Medical Licensing Examination Step 2 clinical knowledge. [ 21 ] These results in the U.S. are generally compatible to this study.…”
Section: Discussionsupporting
confidence: 90%
“…[ 19 , 20 ] Furthermore, one systematic review also showed negative correlation between age and United States Medical Licensing Examination Step 2 clinical knowledge. [ 21 ] These results in the U.S. are generally compatible to this study.…”
Section: Discussionsupporting
confidence: 90%
“…Previous studies conducted for the United States Medical Licensing Examination (USMLE) showed that previous academic achievement was correlated with higher USMLE scores [ 27 ]. A systematic review conducted in 2022 in the USMLE setting also found that step 1 scores, practice examinations, and GPA from high school, all indicators of previous academic achievement, were associated with higher step 2 scores [ 28 ]. Socioeconomic status plays an important role in education; as previously demonstrated by Jacobparayil et al [ 28 ] and Giordano et al [ 27 ], medical students with socioeconomic disadvantages and older age performed worst on USMLE examinations.…”
Section: Discussionmentioning
confidence: 99%
“…Medical school and residency applications include standardised objective measures, such as undergraduate GPA, the Medical College Admission Test (MCAT) or the United Stated Medical Licensing Examination (USMLE), as well as a more holistic review of experiences, extracurriculars and personal attributes. A vast amount of research in the admissions literature has shown a correlation between quantitative academic measures and future success in medical school 2–5 . While admissions committees traditionally have placed greater emphasis on these quantitative academic measures, a holistic review has been shown to confer benefits such as increased diversity of matriculants 6,7 .…”
Section: Introductionmentioning
confidence: 99%
“…A vast amount of research in the admissions literature has shown a correlation between quantitative academic measures and future success in medical school. [2][3][4][5] While admissions committees traditionally have placed greater emphasis on these quantitative academic measures, a holistic review has been shown to confer benefits such as increased diversity of matriculants. 6,7 As such, in recent years the Association of American Medical College has encouraged medical schools to use a holistic review, which they define as a "selection process which takes into consideration applicants' experiences, attributes, and academic metrics as well as the value an applicant would contribute to learning, practice, and teaching."…”
Section: Introductionmentioning
confidence: 99%